Creativity Booster: How Time versus Money Impacts Creative Performances. (6th February 2019) - Gong, Han; Zhou, Haotian; Zhang, Xiao
Abstract: Past research shows that time and money, although both scarce resources indispensable in modern societies, tend to exert distinct impacts on interpersonal behaviors. Yet, little is known about the effects of these two resources on intrapersonal cognitive processes, including creative thinking. In the present research, we explored whether and how increasing the saliency of time versus money concept would affect creative thinking. Six experiments provide converging evidence that activating time concept leads to superior creative performance than money concept. Specifically, individuals treated to time priming (versus money priming) were more likely to solve insight problems (Experiments 1a and 1b), to expand boundaries of conceptual categories (Experiment 2), and to identify connections among seemingly unrelated stimuli (Experiments 3a, 3b and 4). Theoretical and practical implications of these findings are discussed.